Prognostic value of normal sodium levels in patients with metastatic renal cell carcinoma receiving tyrosine kinase inhibitors - Roviello, Giandomenico; Catalano, Martina; De Giorgi, Ugo; Maruzzo, Marco; Buti, Sebastiano; Gambale, Elisabetta; Procopio, Giuseppe; Ottanelli, Carlotta; Caliman, Enrico; Isella, Luca; Sepe, Pierangela; Brighi, Nicole; et al. (Frontiers in Oncology, 2022)
Background: Although serum sodium concentration, in particular hyponatremia, has been shown to be a prognostic marker of survival in metastatic renal cell carcinoma (mRCC), the impact of normal sodium levels has not been investigated. Herein, we investigate the influence of normonatremia in mRCC patients treated with tyrosine kinase inhibitors (TKIs). Materials and methods: For this retrospective study, clinical and biochemical data on patients treated with first line TKIs for mRCC were available from seven Italian cancer centers. We collected natremia levels at baseline and first evaluation after treatment excluding patients with sodium levels outside normal range (<135 or >145 mEq/L). The remaining patients were subdivided into two groups according to median sodium value: natremia patients with <140 mEq/L (n=132) and baseline natremia patients ≥140 mEq/L (n=185). Subsequently, we analyzed the impact of sodium levels on response rate (RR), disease control rate (DCR), progression-free survival (PFS) and overall survival (OS). PFS and OS were estimated through the Kaplan-Meier method and differences between groups examined by the log-rank test. Univariate and multivariate Cox regression was applied to evaluate prognostic factors for PFS and OS. Results: Of the 368 patients, 317 were included in the analysis, 73.1% were males and median age was 67 years (range 36-89). When comparing patients with baseline natremia ≥140 mEq/L (n=185) to patients with natremia <140 mEq/L (n=132), PFS was 15 vs 10 months (p<0.01) and OS was 63 vs 36 months, respectively (p=0.02). On first evaluation, patients with serum sodium ≥140 mEq/L had longer PFS (15 vs 10 months, p<0.01) and OS (70 vs 32 months, p<0.01) than patients with levels <140 mEq/L. Moreover, clinical outcomes showed significant improvement in patients with natremia ≥140 mEq/L compared with patients with levels <140 mEq/L both at baseline and first evaluation: PFS was 19 vs 11 months (p<0.01) and OS 70 vs 36 months (p<0.01), respectively. Conclusions: We found that serum sodium levels <140 mEq/L at baseline and first assessment are independently associated with worse PFS and OS in mRCC patients treated with TKIs in the first-line setting.